Mulch with sugarcane bagasse and bamboo straw attenuates salt stress in cowpea cultivation - Barbosa, Inacio J. [UNESP]; Sousa, Henderson C.; Schneider, Fernanda; Sousa, Geocleber G. de; Lessa, Carla I. N.; Sano, Lamine (Univ Federal Campina Grande, 2021)
This study aimed to evaluate the effect of saline stress on the growth and gas exchange of the cowpea crop in a substrate with and without mulch. The experiment was carried out in Redencao, CE, Brazil. The experimental design was completely randomized in a 5 ? 3 factorial scheme, with five replicates. The treatments consisted of five electrical conductivities of irrigation water (1.0; 2.0; 3.0; 4.0, and 5.0 dS m(-1)) in substrates without and with mulch (sugarcane bagasse and bamboo straw). The analyzed variables were the number of leaves, stem diameter, leaf area, photosynthesis, transpiration, stomatal conductance, water-use efficiency, root dry matter, shoot dry matter, and electrical conductivity of the saturation extract. Using mulch generates positive effects for cowpea shoot growth, regardless of the irrigation water salinity. However, bamboo straw as soil cover minimizes the effects of salts on root dry matter. Soil cover with bamboo straw and sugarcane bagasse minimizes the effects of salts on leaf gas exchange variables, especially at higher electrical conductivity of the irrigation water. Mulches with crop residues from sugarcane bagasse and bamboo straw reduce the electrical conductivity of the soil saturation extract.
Keywords: Vigna unguiculata L.; salinity; soil protection